Pengaruh Lama Pemanasan Terhadap Kadar Alkohol Pada Nira Siwalan (Borassus flabellifer) - siti mardiyah (Universitas Muhammadiyah Surabaya, 2017)
abstractNira is a raw material for the manufacture of liquid brown sugar, palm sugar, and alcoholic beverages. Among these products are the most widely used alcoholic beverage. During this siwalan juice as a beverage consumed fresh, the storage period is relatively short whice for 1-2 days. If after 3 days the beverage is consumed will have a negative impact, to reduce the alcohol content is then made warming. Based on the above background can be taken formulation of the problem